Early administration of interleukin-6 inhibitors for patients with severe COVID-19 disease is associated with decreased intubation, reduced mortality, and increased discharge. (October 2020) - Sinha, Pranay; Mostaghim, Anahita; Bielick, Catherine G.; McLaughlin, Angela; Hamer, Davidson H.; Wetzler, Lee M.; Bhadelia, Nahid; Fagan, Maura A.; Linas, Benjamin P.; Assoumou, Sabrina A.; Ieong, Michael H.; Lin, Nina H.; et al.
Highlights: Observational data on interleukin-6 receptor inhibitors (IL6ri) for COVID-19 disease are reported. IL6ri therapy was found to be associated with improved COVID-19 outcomes. The treatment benefit was greatest when therapy was initiated early during the disease course. IL6ri therapy appears to be superior to remdesivir and dexamethasone. Abstract: Objective: The aim of this observational study was to determine the optimal timing of interleukin-6 receptor inhibitor (IL6ri) administration for coronavirus disease 2019 (COVID-19). Methods: Patients with COVID-19 were given an IL6ri (sarilumab or tocilizumab) based on iteratively reviewed guidelines. IL6ri were initially reserved for critically ill patients, but after review, treatment was liberalized to patients with lower oxygen requirements. Patients were divided into two groups: those requiring ≤45% fraction of inspired oxygen (FiO2 ) (termed stage IIB) and those requiring >45% FiO2 (termed stage III) at the time of IL6ri administration. The main outcomes were all-cause mortality, discharge alive from hospital, and extubation. Results: A total of 255 COVID-19 patients were treated with IL6ri (149 stage IIB and 106 stage III). Patients treated in stage IIB had lower mortality than those treated in stage III (adjusted hazard ratio (aHR) 0.24, 95% confidence interval (CI) 0.08–0.74). Overall, 218 (85.5%) patients were discharged alive. Patients treated in stage IIB were more likely to be discharged (aHR 1.43, 95% CI 1.06–1.93) and were less likely to be intubated (aHR 0.43, 95% CI 0.24–0.79). Conclusions: IL6ri administration prior to >45% FiO2 requirement was associated with improved COVID-19 outcomes. This can guide clinical management pending results from randomized controlled trials.